Gerakan Sosial Politik Meme Pada Media Sosial Instagram Untuk Bali Tolak Reklamasi - Putra, I Gede Bhakti Venda; -, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika, 2018)
ABSTRACT In a technologically advanced era of political movements, it can use "memes" in social media, one of which is shown by the Balinese People Forum refuse reclamation through the use of memes in Instagram social media accounts. The purpose of this research is to know Motivation, ideology and purpose of Forbali movement to do political movements of social media instagram in the form of meme. This study focused on the Forbali political social movement and Instagram account "Forbali13". The method used is qualitative. data collection is done through interviews and document studies. The theory used rests on framed versions of entman analysis and political propaganda as its supporting theories. The findings of the research mentioned that there are, First, there is a hidden purpose of the meme movement in the second Forbali instagram. In Meme Forbali there is a message conveyed, namely the ideology and motivation of movement through social media used to frame the information and education. penyampain from meme done by framing process method in social media of Instagram. Keywords: Meme, Instagram, Forbali, Netizen, and Posting